Managing the increasing returns of a high-tech business model in industry: Classic and ecosystem effects - Svetlana V. Orekhova (Ural State University of Economics, 2020)
Business model management is possible on the basis of detailing and clarifying methods for calculating forms of increasing returns. High-tech companies, in contrast to traditional ones, have additional rents associated with the dual use of technologies and digitalization. The article develops a set of methods for assessing the cumulative increasing returns of a hightech business model based on the calculation of classic and ecosystem effects. The neoclassical economic theory, the network (relational) approach, the concepts of business models and ecosystems constitute the methodological basis of the study. The authors differentiate between five forms of returns: economies of scale effects, effects of innovation, diversity, direct and indirect network-based (ecosystem) effects. The research method is pioneered by the authors and based on a sequential assessment of the five forms of returns. For each form, an optimal calculation method is proposed, the results of which are unified by the standardization method. The level of increasing returns is empirically calculated using the case study of the civil production of the Semikhatov Scientific and Production Association (SPA) of Automatics – one of the largest high-tech industrial enterprises. The paper highlights the problems in measuring returns, such as the lack of panel data on the enterprise, a uniform method and relevant examples for calculation, as well as objective data on sectoral markets. The research results prove that the key management objective is to enhance the positive difference between increasing and decreasing returns through transformation of the business model. To achieve this objective, we compile a matrix of effects, the level of which allows making appropriate management decisions. Our calculations show that the enterprise experiences decreasing returns from adoption of innovation. The level of increasing returns from the learning effect and the direct network-based effect is quite low, which indicates that the enterprise’s business model is traditional, rather than technological. The research results can serve as a basis for the development of a detailed management mechanism for transforming a business model. The method for increasing returns assessment is universal and can be applied to evaluate the effectiveness of any business models.